Rancang Bangun Gim Edukasi Materi KPK dan FPB Menggunakan Metode Multimedia Development Life Cycle - Bata, Julius (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2023)
Educational games have developed as a promising alternative to traditional learning approaches and are now widely used in various educational settings. Empirical research has demonstrated that adopting educational games as educational tools improves students' learning and motivation, especially in mathematics. This study aims to design and develop an educational game for elementary school mathematics learning, especially the topics of Least Common Multiple (LCM) and Greatest Common Divisor (GCD). For this purpose, we apply the Multimedia Development Life Cycle, which consists of six steps: concept, design, material collecting, assembly, testing, and distribution. The game was developed by using the Unity game engine and tested using black box testing. As a result, all the primary functions in the game were valid. For future studies, we intend to conduct user studies with elementary students.